Study on detection of intracerebral hemorrhage based on frequency difference of permittivity - Peng, Shixin; Wang, Xiaoshu; Jin, Gui; Wang, Feng; Zhu, Ji; Zhang, Xiaodong; Liu, Nan; Xu, Rui (Frontiers in Physics, 2023)
Current detection of intracerebral hemorrhage (ICH), whether employing Electrical Capacitance Tomography (ECT) or other electrical imaging techniques, rely on time-difference measurements. The time-difference methods necessitate baseline measurements from the patient in a non-hemorrhagic state, which is impractical to obtain, rendering rapid detection of ICH unfeasible. This study introduces a novel approach that capitalizes on the distinct dispersion characteristics of the permittivity in brain tissue and the spectral variance of the permittivity between blood and other brain components. Specifically, the frequency-dependent variations in the permittivity are employed to achieve absolute detection of ICH, thereby eliminating the need for non-hemorrhagic baseline data. The methodology entails identification of two frequency points that the frequency-dependent variation in the permittivity at these two frequency points manifest the maximal difference between blood and other brain tissues. Subsequently, this permittivity differential at the two identified frequency points is utilized for hemorrhage detection. Experimental measurements were conducted using an impedance analyzer and a parallel plate capacitor to capture the capacitance in four single-component substances-distilled water, sheep blood, isolated pig fat, and isolated pig brain-as well as three mixed blood compounds-distilled water enveloping sheep blood, pig fat encapsulating sheep blood, and pig brain surrounding sheep blood-across a frequency range of 10 kHz to 20 MHz. The results show that in different frequency bands, it is indeed possible to distinguish single-component substances from mixed substances by the frequency difference of capacitance variation. Comparative analysis reveals that the 1MHz to 5MHz frequency range is most effective for detecting blood in distilled water. For blood detection in pig fat, a 10kHz to 1MHz frequency range is identified as optimal, while a 10kHz to 0.5MHz frequency range is advantageous for blood detection in pig brain tissue. The findings confirm that absolute detection of ICH is achievable through frequency-dependent variations in the permittivity. However, this necessitates the identification of the frequency band manifesting the largest difference of frequency-dependent variation between single-component and mixed substances.